Relationship between lunch box quality and salivary pH in schoolchildren of a primary educational institution, Peru, 2023 - Chávez-Fernández, Damaris Katherin; Rendón-Alvarado, Alfredo Carlos Manuel (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Introduction: The intake of certain foods can favor or affect oral health since those with a high proportion of glucose, sucrose, and starch produce more acids and have a high adhesiveness, slowing down their elimination and leading to the appearance and proliferation of carious lesions due to the spread of acid in the teeth, prolonged retention, or variation in the salivary pH level. The objective of the study was to determine if there is a relationship between the quality of the lunch box and salivary pH in schoolchildren in the fifth grade of primary school at the Inmaculada Concepción Public Educational Institution from Monsefú, during the year 2023. Methods: The design was descriptive with analytic and correlational purposes. The sample was made up of 123 fifth-grade primary school students from the I.E.P.; saliva samples were taken four times, before and after consuming their lunch box, whether healthy or not, determining their salivary pH according to age and sex. Descriptive analysis was applied, as well as regression and variance analysis. Results: Schoolchildren with a healthy lunchbox had a neutral salivary pH at 5 minutes (average: 6.5), 30 minutes (average: 6.8), and 60 minutes (average: 6.9) after eating the lunchbox, unlike those with an unhealthy lunchbox, who had an acidic salivary pH at 5 minutes (average: 5.7), 30 minutes (average: 6.0), and 60 minutes (average: 6.1). Conclusion: There is a positive and moderate correlation between salivary pH and the type of school lunchbox ingested by the schoolchildren studied.